Analysis of the Meaning of Joy (Al-Farh) According to the Al-Qur'an Perspective of Tafsir Al Munir - Mus'ab Marbun; Uqbatul Khoir Rambe (al-Afkar, Journal For Islamic Studies, 2025)
Joy (Al-Farh) in the Koran has various meanings, which can include temporary worldly joy or eternal spiritual joy. In the perspective of al-Munir's tafsir, the word farh is understood as a form of feeling happy or joyful which is often related to worldly or spiritual circumstances. Tafsir al-Munir presents an in-depth analysis of the difference between temporary and eternal joy, emphasizing that joy derived from worldly achievements, such as wealth, power, or pleasure, is often deceptive and leads to arrogance and negligence towards the afterlife. For example, the story of Qarun in Surah Al-Qasas (28) verse 76 illustrates how worldly joy can be misleading if accompanied by arrogance. On the contrary, this tafsir highlights the joy that comes from piety and obedience to Allah as true happiness that not only brings peace in worldly life, but also guarantees eternal happiness in the afterlife. In al-Munir's tafsir, true joy is measured by the depth of a person's faith and relationship with Allah, which leads to a nobler purpose in life. Therefore, this tafsir reminds Muslims not to be trapped in temporary worldly joy, but rather to pursue eternal joy through devotion to Allah. True joy is that which gives peace of mind and leads to eternal happiness in heaven, not temporary and misleading.